Application of Authentication Evaluation Techniques of Ethnobotanical Medicinal Plant Genus Paris: A Review. (2nd September 2020) - Pei, Yifei; Zhang, Qingzhi; Wang, Yuanzhong
Abstract: Genus Paris mainly distributed in Asia and served as traditional ethnobotanical medicine in China, India, and Nepal. The main aim of this study was to review ethnic minorities medicinal records for Paris in China, the Chinese patent medicines based on Paris materials and the authentication and quality evaluation of Paris based on two parts of analytical technologies and data analysis. This article reviews approximately 100 articles from 1980 to 2019 published on the research of genus Paris materials and their Chinese patent medicines. Additionally, local books were also searched. Five major kinds of chemical techniques have been applied to authentication and quality assessment of Paris and among them, chromatography was the most widely used one, and DNA barcoding technique was the most worth further study. Additionally, more than 70% of the research studies were analyzed by unsupervised pattern-recognition techniques combined with analytical technologies such as spectroscopy. Meanwhile, the data fusion strategy with higher classification ability combined multiple supervised pattern-recognition techniques have been gradually applied to authentication assessment. The optimal analytical technologies and methods applied to Paris qualities for authentication and quality evaluation are greatly important, which could promote the development and utilization for ethnomedicines of Paris .